Marcas do discurso da matemática escolar: uma investigação sobre as interações discursivas nas aulas do ensino médio - Airton Carriao Machado (2008)
The present investigation aimed at identifying speech hallmarks characteristics of Mathematics classrooms speeches. We oriented our work by Bakhtins perspective of speech, particularly the concept of speech genres and discursive sphere. In order to do a broader analysis of the social context, we refer to Bourdieus concepts of habitus, cultural capital and field. With these concepts, we started an observation of ethnographic character. It took place in a Brazilian federal technical school. We observed a first year and a last year high school classes. Seeking to explain the ideologies present in the Mathematics classroom, we observed the need to study the academic mathematics field, mainly the constitution of the mathematics formalist perspective, which has a strong influence of the teaching of the subject. To situate this research in the main perspectives of the theme in Mathematics Education, we mapped the diverse research conceptions of the mathematics classroom speech. The analysis of the observed data revealed that the social positions have an important role in the delineation of speech genres. As a result we conducted a study of the social position arrangement in the field of the analyzed classrooms. We verified an asymmetry of classroom power. Finally, we identified some speech hallmarks that we considered being determinants in the constitution of the genres presents in Mathematics classroom. They are nominalization, how to and oral/written relationship.